2014
DOI: 10.1161/circulationaha.113.003334
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracy of Estimated Resting Oxygen Uptake in the Clinical Setting

Abstract: Hence, we assessed the accuracy of estimated resting VȮ 2 compared with measured VȮ 2 obtained by the gold-standard analysis of timed collections of exhaled air by the method of Douglas in a large population of consecutive adult patients who underwent right-heart cardiac catheterization for clinical indications at our hospital. Clinical Perspective on p 210Background-The Fick principle (cardiac output = oxygen uptake (VȮ 2 )/systemic arterio-venous oxygen difference) is used to determine cardiac output in nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 23 publications
(33 reference statements)
1
48
0
3
Order By: Relevance
“…First, the Fick principal is often applied to determine cardiac output by the use of an estimate of O 2 uptake. This introduces important error, and O 2 uptake should be measured directly at the time of catheterization 17,18 ; dilution methods are appropriate only in the absence of intracardiac shunting. Second, catheterization data represent a snapshot of supine resting hemodynamics at a single moment in time.…”
Section: Diagnosis: Cardiac Catheterizationmentioning
confidence: 99%
“…First, the Fick principal is often applied to determine cardiac output by the use of an estimate of O 2 uptake. This introduces important error, and O 2 uptake should be measured directly at the time of catheterization 17,18 ; dilution methods are appropriate only in the absence of intracardiac shunting. Second, catheterization data represent a snapshot of supine resting hemodynamics at a single moment in time.…”
Section: Diagnosis: Cardiac Catheterizationmentioning
confidence: 99%
“…Specifically, applying the indirect Fick technique leads to a high likelihood of inaccuracy in cardiac output, as results are frequently based on estimated values (rather than direct measurements) for oxygen uptake due to the time-consuming nature of the measurement and the expensive equipment required for the direct method [3,33]. This was clearly illustrated in a study of 535 adult patients undergoing RHC in whom resting oxygen uptake was assessed using estimated values according to three published formulae, or by direct assessment through timed collections of exhaled air via the Douglas bag technique [33]. Results from the study demonstrated a >25% difference between directly measured and estimated values in 17-25% of patients, depending on the formula used to derive the estimated values [33].…”
Section: Pitfalls In Measurement Of Cardiac Outputmentioning
confidence: 99%
“…This was clearly illustrated in a study of 535 adult patients undergoing RHC in whom resting oxygen uptake was assessed using estimated values according to three published formulae, or by direct assessment through timed collections of exhaled air via the Douglas bag technique [33]. Results from the study demonstrated a >25% difference between directly measured and estimated values in 17-25% of patients, depending on the formula used to derive the estimated values [33].…”
Section: Pitfalls In Measurement Of Cardiac Outputmentioning
confidence: 99%
“…Numerous studies demonstrated limited agreement of direct VO 2 measurements with VO 2 estimations 5 6. It has therefore been argued that VO 2 should always be measured and not estimated.…”
Section: Equations For Vo2 Estimationmentioning
confidence: 99%